Channel Mobility and Contact Resistance in Scaled ZnO Thin-Film Transistors - Alnazer Mohamed (Solid-State Electronics, 2020)
ZnO thin-film transistors (TFTs) with scaled channel lengths of 10 m, 5 m, 4 m, and 2 m exhibit increasing intrinsic channel electron mobility at a gate bias of 10 V (15 V) from 0.782 cm/Vs (0.83 cm/Vs) in the 10 m channel length TFT to 8.9 cm/Vs (19.04 cm/Vs) for the channel length scaled down to 2 m. Current-voltage measurements indicate an n-type channel enhancement mode transistor operation, with threshold voltages in the range of V to V, maximum drain currents of 41 A/m, 96 A/m, 193 A/m, and 214 A/m at a gate bias of 10 V, and breakdown voltages of 80 V, 70 V, 62 V, and 59 V with respect to channel lengths of 10 m, 5 m, 4 m, and 2 m. The channel electron mobility (excluding contact resistance) is extracted by the transmission line method (TLM) from the effective electron mobility (including contact resistance). The contact sheet resistance of /sq extracted from the measurements, which is larger than the contact sheet resistance of /sq obtained from the DFT calculation and the 1D self-consistent Poisson-Shrödinger simulation, largely limits the drive current in the scaled ZnO TFTs.